2022
DOI: 10.3390/horticulturae8090756
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Based Identification, Characterization, Evolutionary Analysis, and Expression Pattern Analysis of the WRKY Gene Family and Salt Stress Response in Panax ginseng

Abstract: WRKY transcription factors are some of the most important transcription factors in planta, and they are involved in biological and abiotic stresses, growth and development, and biochemical processes. The WRKY gene family has been found in many higher plants, while little is known about WRKY-encoding genes in ginseng. As a traditional and important economic medicinal herb and health food, ginseng has been a model species for other related medicinal plants. Here, we analyze the WRKY transcript factor gene family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…In Arabidopsis thaliana, the corresponding numbers were thirteen, four, eight, and seven [10], while in B. pervariabilis × D. grandis, they were three, four, six, and eight. These findings imply that the BBX gene may have originated from a common ancestor in several species and independently spread following the divergence of dicotyledons and monocotyledons [36].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In Arabidopsis thaliana, the corresponding numbers were thirteen, four, eight, and seven [10], while in B. pervariabilis × D. grandis, they were three, four, six, and eight. These findings imply that the BBX gene may have originated from a common ancestor in several species and independently spread following the divergence of dicotyledons and monocotyledons [36].…”
Section: Discussionmentioning
confidence: 86%
“…The GO database is a widely used tool for standardizing the functional classification of genes in transcriptome analyses [36]. Studies have shown that members of the BDBBX gene family exhibit different functions.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, transcription factors with binding function and can be to other proteins domain or DNA sequence promoter region to perform their specific functions [ 2 ]. Currently, the GRAS [ 3 , 4 ], AP2/ERF [ 5 ], MYB [ 6 ], WRKY [ 7 ], NF-Y [ 8 ], HD‑Zip [ 9 ], bHLH [ 10 ], and other specific transcription factor families have been bioinformatically analysed, and their functions have been verified in ginseng. The trihelix transcription factor had been functionally validated in many plants, but no in-depth reports or systematic studies about this gene family in ginseng.…”
Section: Introductionmentioning
confidence: 99%